2024
DOI: 10.1245/s10434-024-15456-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Online Risk Calculator for Sentinel Node Positivity on Management of Patients with T1 and T2 Melanomas

Alec A. Winder,
Zoe Boyer,
Sydney Ch’ng
et al.

Abstract: Background Predicting which patients with American Joint Committee on Cancer (AJCC) T1–T2 melanomas will have a positive sentinel lymph node (SLN) is challenging. Melanoma Institute Australia (MIA) developed an internationally validated SLN metastatic risk calculator. This study evaluated the nomogram’s impact on T1–T2 melanoma patient management at MIA. Methods SLN biopsy (SLNB) rates were compared for the pre- and post-nomogram periods of 1 July 2018–30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Our study 5 of the host institution’s experience showed the introduction of the MIA calculator was associated with an increased rate of SLNB for patients with “calculator defined higher risk” T1a melanomas with indications of an increase in SLN metastasis detection for this group. There was also a trend towards patients with higher risk T1b melanomas to undergo more SLNBs and those with lower risk T2a melanomas to undergo less.…”
Section: Pastmentioning
confidence: 82%
“…Our study 5 of the host institution’s experience showed the introduction of the MIA calculator was associated with an increased rate of SLNB for patients with “calculator defined higher risk” T1a melanomas with indications of an increase in SLN metastasis detection for this group. There was also a trend towards patients with higher risk T1b melanomas to undergo more SLNBs and those with lower risk T2a melanomas to undergo less.…”
Section: Pastmentioning
confidence: 82%